The proposed Technical Instruction Bill, and the science and art department - Coffey, George (Statistical and Social Inquiry Society of Ireland, 1889)
Much dissatisfaction has been expressed from time to time with the Science and Art, or, as it is generally called, South Kensington system, and in the report of the late Commission on Technical Instruction, the department receives but scant praise. It is, therefore, very desirable that the question as to how far the system and methods of the Science and Art Department are applicable to technical education, should be carefully considered before any extension of the system in that direction is decided on. The South Kensington system is essentially a centralised system, whereas technical and industrial education would appear to necessitate local freedom and development of instruction in accordance with local needs. In this respect the continental and English systems are quite at variance?technical and industrial education on the continent being, in general, controlled and determined by local requirements. Following out this line of discussion, I believe the inefficiency of the Science and Art Department can be shown to be almost entirely due to centralisation, and my object is to raise the question, with reference to the proposed Technical Instruction Bill, of the practicability of promoting technical education through the agency of that department.
Read 19th February, 1889
Keywords: Technical education; Technical instruction bill; 314.15